Development of snow-blowing structures for protection roads from snow drifts - D. N. Sannikov; V. V. Servatinsky (Вестник СибАДИ)
Introduction. The article discusses the use of the snow blowing method and the possibility of installing snowblowing structures on highways to protect against snow drifts. The problem of snow tolerance is identified due to the location of many highways in remote, hard-to-reach areas and difficult climatic conditions. Snow drifts significantly increase the cost of winter maintenance of roads, are a partial consequence of destruction and maintenance in the summer, and also pose a serious threat to safety, causing loss of control over the vehicle.Research methodology. The article discusses the application of the snow blowing method and the possibility of installing snow-blowing structures on roads to protect against snow drifts. The process of movement of snow particles in a snowstorm and the influence of these processes on snow blowing are considered.Results. The paper highlights the issues related to the analysis and assessment of the speed and composition of the air flow, weather conditions affecting the operation of structures. The main purpose and working conditions of snow-blowing structures on highways have been determined. The optimum speed at which the snow blowing effect is created is determined.Conclusion. The snow blowing process on the developed snow blowing structure in different conditions is modelled. Based on the considered approach, a comparative analysis of the operation of the snow blowing structure is performed. Based on the data obtained, the possibilities for the introduction of snow-blowing structures and refinement in real working conditions have been studied.